2013
DOI: 10.1590/s2317-17822013005000008
|View full text |Cite
|
Sign up to set email alerts
|

Singing voice handicap mapped by different self-assessment instruments

Abstract: The questionnaires developed for the assessment of singing voice, S-VHI and MSVH, showed to be more specific and correspondent to each other for the evaluation of vocal handicap in singers. Findings showed that the more the time of singer's singing experience, the smaller the handicap is. Gender and singing styles did not influence the perception of the handicap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
0
6
0
9
Order By: Relevance
“…In 2007, an American group of researchers proposed a validated questionnaire, entitled Singing Voice Handicap Index (S-VHI) (11) . In Portuguese this questionnaire is called Índice de Desvantagem Vocal para o Canto (IDV-C) (12) . This questionnaire evaluates the physical, emotional, social and economic impact of voice problems in singers.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, an American group of researchers proposed a validated questionnaire, entitled Singing Voice Handicap Index (S-VHI) (11) . In Portuguese this questionnaire is called Índice de Desvantagem Vocal para o Canto (IDV-C) (12) . This questionnaire evaluates the physical, emotional, social and economic impact of voice problems in singers.…”
Section: Introductionmentioning
confidence: 99%
“…One study (15) found that, the longer the time of experience in singing, the lower the vocal disadvantage measured by the Classical Vocal Handicap Index (IDVCC). Other studies have found that the correlation between the time in the profession, the total score (16) and the three subscales of the MSHI (9) was negative, that is, there is a greater vocal disadvantage among singers with shorter career period. On the other hand, other studies did not find a significant statistically association in the correlation between career time and vocal disadvantage of lyrical and popular singers (17) and Church Singers (12) The results of this study also showed that singers who do not alternate the songs with another singer, during the shows, have a greater vocal disadvantage, in relation to the singers who alternate.…”
Section: Discussionmentioning
confidence: 91%
“…Research has shown that the use of generic self-assessment protocol identifies lower vocal disadvantage in their singers, when there is some specific information directed to singing, including the Modern Singing Handicap Index -MSHI. Thus, to assess the impact of the voice problem on the lives of singers, it is necessary to use the specific protocol for this group (9) .…”
Section: Introductionmentioning
confidence: 99%
“…The use of standardized and validated protocols favors speech therapy practice as it facilitates the comparison of results between different services and allows the realization of studies that direct and improve procedures, which contributes to evidence-based practice and provides better quality of care to the patient (1)(2)(3)(4) .…”
Section: Introductionmentioning
confidence: 99%